2011
DOI: 10.1021/jp2048162
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Size Dependence of the Optical Properties of Tetrapod-Shaped Colloidal Nanocrystals Exhibiting Type-II Transitions

Abstract: We have investigated the optical properties of colloidal seed-grown CdSe (seed)/CdTe (arms) nanotetrapods both experimentally and computationally. The tetrapods exhibit a type-II transition arising from electrons localized in the CdSe seed region and holes delocalized in the CdTe arms, along with a residual type-I recombination in long-arm tetrapods. Experiments and theory helped to identify the origin of both types of transitions and their size dependence. In particular, time-resolved experiments performed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 77 publications
1
21
0
Order By: Relevance
“…8(b and c) shows the dependences of the PL-peak energy (E peak ) on a cubic root of P ex (denoted as P 1/3 ex ). It comes to our attention that these dependences are linear, which is a typical token usually found in type-II heterostructures [14,35,45]. However, if observing carefully the P 1/3 ex dependences of E peak , one can see that the slope of the linear lines is quite small.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…8(b and c) shows the dependences of the PL-peak energy (E peak ) on a cubic root of P ex (denoted as P 1/3 ex ). It comes to our attention that these dependences are linear, which is a typical token usually found in type-II heterostructures [14,35,45]. However, if observing carefully the P 1/3 ex dependences of E peak , one can see that the slope of the linear lines is quite small.…”
Section: Resultsmentioning
confidence: 64%
“…Here, the blue shift of E peak as increasing P ex is due to the screening of an internal-electrical field generated by the charge separation under intense photogeneration in the vicinity of the core/shell interface because of the storage of carriers near the interface. This field induces a band bending near the contact surface between two materials and a consequent blue shift of the original type-II transition because the transition originates mainly from recombination of carriers located at the interfacial region [14,59]. If noticing the E peak (P 1/3 ex ) curves in Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…162 Further studies on semiconducting tetrapodal heterostructures such as CdSe (seed)/CdTe (arms) demonstrated that these tetrapods exhibit a type-II transition arising from electrons localized in the CdSe seed region and holes spatially separated in the CdTe arms, alongside with a residual type-I recombination in long-arm tetrapods ( Figure 13). 72 Owing to this band alignment, the tetrapodal heterostructures display a type-II transition in the infrared region and a type-I visible transition arising from direct recombination occurring exclusively in the CdTe arms. Time-resolved PL measurements on both type-I and type-II emissions have proven the various degrees of electron-hole wave function localization occurring in tetrapods with different arm lengths.…”
Section: Solar Cellsmentioning
confidence: 99%
“…The researchers have also demonstrated that the type-II transition sustains electron promotion from the core region to the arm conduction band. 72 The unique tunability of the arm length and the bandgap is very attractive for the application of tetrapods in various hybrid solar cells. 19,161 In polymer-inorganic hybrid solar cells, quantum dot NCs serve as the electron acceptors and a conjugated polymer (e.g., poly(3-hexylthiophene-2,5-diyl), P3HT) as electron donors.…”
Section: Solar Cellsmentioning
confidence: 99%